2003
DOI: 10.1182/blood-2003-01-0072
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the intrinsic properties of the GPIbα–VWF tether bond define the kinetics of the platelet-type von Willebrand disease mutation, Gly233Val

Abstract: Platelet-type von Willebrand disease (PT-VWD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 37 publications
9
51
1
Order By: Relevance
“…5). These results are consistent with their respective GOF and loss of function phenotypes found in other assays, explaining the spontaneous binding of VWF to platelet for type 2B VWD (50,51) and ptVWD (42)(43)(44), as well as the ineffective binding of VWF to platelet for type 2M VWD (22,52) …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…5). These results are consistent with their respective GOF and loss of function phenotypes found in other assays, explaining the spontaneous binding of VWF to platelet for type 2B VWD (50,51) and ptVWD (42)(43)(44), as well as the ineffective binding of VWF to platelet for type 2M VWD (22,52) …”
Section: Discussionsupporting
confidence: 79%
“…We also studied a ptVWD mutant GPIb␣ (G233V) captured from lysates of G233V CHO␣␤9 cells. Consistent with its GOF phenotype in other assays (42)(43)(44), the lifetime versus force curve of 1238-A1 bonds with GPIb␣G233V (Fig. 5C, black) was significantly upshifted relative to that with WT GPIb␣ (Fig.…”
Section: Soluble Gln 1238 -Glu 1260 Reduces Gpib␣ Bond Lifetimes Withsupporting
confidence: 65%
“…27,34 The dissociation rate constants of transient tethers to wtDЈA3 were of the same order of magnitude as reported, although previous studies used isolated bacterial A1 domains at lower shear rates. 27,35,36 Interestingly, no significant difference in the dissociation rate constants for bonds formed between platelets and OLG mutants were detected compared with wtDЈA3. This excludes an effect of OLG on VWF-platelet dissociation as an explanation for the increased translocation rates.…”
Section: Org Frommentioning
confidence: 99%
“…2a). It has been shown that the probability P a for a cell to tether before it flows a distance x over the surface is: 11 (1) where the probability p ad for a cell to tether per unit distance is: 21 (2) where ϕ is the collision frequency and 2πrl c t c = 〈A i t i 〉 is cross-correlation of contact area and contact time. Tether rate (TR) is defined as the ratio of the number of tethering events to the total number of cells flowing through the field of view of length L in a given period (e.g., 1 min).…”
Section: Conceptual Scheme Of Tethering Processmentioning
confidence: 99%